Efeitos do ultrassom terapêutico sobre a função endotelial: revisão sistemática e metanálise - Rubin Neto, Léo José (2024)
The vascular endothelium is the largest biological sensor and its function is responsible for the maintenance and homeostasis of blood vessels, which includes blood coagulation, adhesion and aggregation of leukocytes and platelets, regulation of tone, growth and vascular permeability. Endothelial dysfunction is a predictor of cardiovascular events and mortality. Interventions that improve endothelial function have effects on vascular homeostasis. The effects of low-intensity therapeutic ultrasound on endothelial function have been studied, as well as its action on the formation of nitric oxide and the inflammatory process. This research comprises a systematic review that aimed to evaluate the effects of low-intensity therapeutic ultrasound on endothelial function in humans. The search strategy was performed in the MEDLINE, Cochrane CENTRAL, SCIELO, EBSCO, EMBASE, and Web of Science databases, with the descriptors “Ultrasonic Therapy” and “Nitric Oxide”; “Endothelium-Dependent Relaxing Factors”; “Vascular Stiffness”; "Receptors, Vascular Endothelial Growth Factor"; "Blood Flow Velocity"; "Endothelium, Vascular"; "Plethysmography"; "Forearm”; "Vasodilation”; "Brachial Artery”; “Flow-Mediated Dilation” and "Hyperemia". The search was conducted without restriction of language or year of publication. The inclusion criteria were randomized clinical trials evaluating endothelial function in humans. The data were presented descriptively, and a meta-analysis was performed using the randomized model, with the mean difference (MD) and their respective 95% confidence intervals (95% CI) as measures of effect size. The risk of bias was assessed using the Cochrane RoB 2.0 tool.